Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1295/polymj.pj2006129
|View full text |Cite
|
Sign up to set email alerts
|

Living Ring-Opening Metathesis Polymerization of Exo-Norbornenes Bearing Both Cyano and Ester Functionalities by a Well-Defined Ruthenium Catalyst

Abstract: ABSTRACT:Exo-ethyl 3-cyanobicyclo[2.2.1]hept-5-ene-2-carboxylate (A) and exon butyl 3-cyanobicyclo[2.2.1]-hept-5-ene-2-carboxylate (B) bearing both cyano and ester groups were subjected to homopolymerization by ringopening metathesis polymerization with a well-defined Ru catalyst, (H 2 IMes)(3-bromopyridine) 2 Cl 2 Ru=CHPh (3) (H 2 IMes = N,N 0 -bis(mesityl)-4,5-dihydroimidazol-2-ylidine) at low temperature. The characterization of the synthesized homopolymers by GPC analyses showed a value of a number-average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…1) enables both high reactivity and precise specification of chain lengths, with polydispersities as low as 1.02 at À15 8C affording the corresponding ring-opening metathesis polymers in a living manner. 84 The Slugovc et al, [85][86][87] Choi and Grubbs, 88 and Kiessling and coworkers 54 also recently reported that related catalysts to 2 can be involved in this category as outstanding Ru initiators for ROMP. These results prompted us to investigate the living polymerization of various doubly functionalized norbornenes 3a-3g, with different substituents in the ester groups, as shown in Figure 1.…”
Section: Results and Discussion Polymerization Characterization Anmentioning
confidence: 99%
“…1) enables both high reactivity and precise specification of chain lengths, with polydispersities as low as 1.02 at À15 8C affording the corresponding ring-opening metathesis polymers in a living manner. 84 The Slugovc et al, [85][86][87] Choi and Grubbs, 88 and Kiessling and coworkers 54 also recently reported that related catalysts to 2 can be involved in this category as outstanding Ru initiators for ROMP. These results prompted us to investigate the living polymerization of various doubly functionalized norbornenes 3a-3g, with different substituents in the ester groups, as shown in Figure 1.…”
Section: Results and Discussion Polymerization Characterization Anmentioning
confidence: 99%
“…This tendency is consistent with the previous studies by us 9 and others. 13,15 When the reaction time took more than 18 hours, the M n values and the PDIs increased with the reaction time (data not shown). Polymer 2a was obtained with a high yield (76%) and narrow PDI (1.08) at −15 °C under the same reaction conditions as 1a (Table 1, entry 4), which is better than the reported ROMP of 1 and 2 with the Ru-based catalysts 16 and the Mo-based catalysts 17 (1.2–1.8 of PDI values).…”
Section: Resultsmentioning
confidence: 92%
“…After enantioseparation, the obtained monomers It has been widely known that third generation Grubbs initiator (H 2 IMes)(3-bromopyridine) 2 Cl 2 Ru¼ CHPh (3) 41 (H 2 IMes ¼ N,N 0 -bis(mesityl)-4,5-dihydroimidazol-2-ylidine) exhibits better control due to faster initiation and inhibits side reaction like back-biting. 42 We have also previously reported that the Ru catalyst 3 promotes living ROMP for a polar norbornene 1 with both higher activity and better molecular weight control, 43 although the used monomers were racemic. Thus above separated optically active norbornenes (þ)-1 and (-)-1 were subjected to the polymerization by the Ru catalyst 3 in CH 2 Cl 2 at À15…”
Section: Resultsmentioning
confidence: 92%